Feeding of silverside (Odontesthes bonariensis) in Bajo Giuliani and Don Tomás Shallow lakes, La Pampa Province, Argentina (Semiárida, 2018)
Shallow lakes are found in the Eastern region of La Pampa province which were stockedwith Odontesthes bonariensis, becoming a fish catchment opportunity. Such a fish species exhibits a preference for plankton as food, but if that resource were scarce, other kind offeeds can be included in its diet as a consequence of its feeding plasticity. Diet compositionvaries according to fish size, with occurrence of cannibalism at an old age. The objectiveof this work was to assess the percentage diet composition by the total number of individuals, and by body size, of O. bonariensis feeding in the shallow lakes of Bajo Giuliani and Don Tomás. Catchment of fish was performed using gillnets of different mesh sizes. Stomachs removed from fish were fixed in 10% formol, and their contents were observed withstereoscopic optical microscope. Prey volume and its frequency of occurrence were measured. Ten types of preys in Bajo Giuliani lake, and 6 in Don Tomás lake, were identified. In both environments, the plankton was the main food for fish smaller in size, whereas the biggest ones turned out to be piscivores. Jenynsia multidentata was the most predatedfish. It is considered necessary to carry out a study that allow surveying fish trophic behavior throughout the year.
Keywords: Odontesthes bonariensis; feeding; shallow lakes; La Pampa